Extending the Shelf Life of Paddy Straw Mushroom (Volvariella volvacea) with Chemical Treatment - , Sagarika Giri; , Anita Priyadarsini; , Niranjan Chinara (Archives of Current Research International, 2025)
Volvariella volvacea commonly referred as paddy straw mushroom, holds a significant place among edible mushroom and is cultivated using a wide range of substrate. It cultivated primarily in tropical and subtropical regions due to their rapid growth, high nutritional value and consumer preference. These mushrooms are known for their high perishability due to their very short shelf life about 12 hours that limit storage, transportation and distribution, leading to rapid post-harvest deterioration and reduced market availability. The study was conducted in Centre of Tropical Mushroom Research and Training (CTMRT), OUAT, Bhubaneswar, to investigate the potential of various chemical preservatives to enhance the shelf life of these mushrooms. Sodium benzoate (0.05%) and Potassium meta-bisulphite (0.05%) was found effective in enhancing the shelf life of paddy straw mushrooms up to 24 hours and retain the normal colour and odour.